OVERVIEW OF THE PLANNING DOCUMENT STRUCTURE AS A TOOL FOR LOCAL GOVERNMENT PERFORMANCE MEASUREMENT AND RISK MANAGEMENT - Erafat, Yasiir; Lestari, Winda Rika (Universitas Dharma Wacana, 2024)
Local governments have a noble role in providing direct services felt by the community regarding basic needs such as civil registration services for primary and secondary education, health care, etc. by paying attention to the synchronization of policies at the central and provincial government levels. To ensure the effectiveness of the execution of these functions, local governments should adopt a performance management and risk management approach as formulated in applicable laws and regulations to improve the quality of strategic management in line with the principles of good governance. Based on these matters, by taking into account the applicable laws and regulations and taking into account the span of control of local government organizations, it is very necessary to identify detailed activities and/or end products documented in the annual planning document, especially at the Regional Apparatus Organization (OPD) level, detailed activities and/or end products describe in detail the sub-activities and sub-activity indicators, the identification and documentation can improve the quality of the OPD annual planning document as a living document, because it is not only used as a basis for measuring performance, but also as an input in identifying and analyzing risks at the operational level in achieving performance objectives at the sub-activity level, and can be used as an input in ensuring the cascade preparation of performance agreements from both the strategic level and the operational level. The methodology of this research uses a descriptive qualitative approach focusing on the Statute Approach and the Conceptual Approach